Adsorption of gentian violet dyes in aqueous solution on microporous AlPOs molecular sieves synthesized by ionothermal method. (14th February 2018) - Fortas, W; Djelad, A; Hasnaoui, M A; Sassi, M; Bengueddach, A
Abstract: In this work, AlPO-34, like-chabazite (CHA) zeolite, was ionothermally prepared using the ionic liquid (IL), 1-ethyl-3-methylimidazolium chloride [EMIMCl], as solvent. The solids obtained were characterized by x-ray powder diffraction (XRD), scanning electron microscopy (SEM), infrared spectroscopy (FTIR), thermal analysis (TG) and nitrogen adsorption/desorption at 77.3 K. The results show that the ionic liquid is occluded in the AlPO-34 framework and consequently it acts also as a structure-directing agent. The variation of chemical composition led to AlPO-34 materials with different crystal sizes and morphologies. The well crystallized AlPO-34 material was used as adsorbent for Crystal Violet (CV) dye removal from aqueous solutions. The effect of adsorption parameters such as pH and initial concentration were investigated. It was found that adsorption dyes is favorable at pH = 6. The adsorption isotherm data follow the Langmuir equation in which parameters are calculated. The selected AlPO-34 sample exhibited a high crystal violet dye removal of 46.08 mg g −1 at pH = 6.